Water Exchange between Deep Basins of the Bransfield Strait - Dmitry I. Frey; Viktor A. Krechik; Eugene G. Morozov; Ilya D. Drozd; Alexandra S. Gordey; Alexander A. Latushkin; Olga S. Mekhova; Rinat Z. Mukhametianov; Svetlana A. Murzina; Sofia A. Ostroumova; Vladimir I. Ponomarev; Pavel A. Salyuk; et al. (Water, 2022)
The Bransfield Strait is a relatively deep and narrow channel between the South Shetland Islands and the Antarctic Peninsula contributing to the water transport between the Pacific and Atlantic sectors of the Southern Ocean. The strait can be divided into three deep separate basins, namely, the western, central, and eastern basins. The sources of deep waters in the three basins are different, leading to differences in thermohaline properties and water density between the basins. The difference in water density should in turn cause intense deep currents from one basin to another through narrow passages over the sills separating the basins. However, there are still no works dedicated to such possible overflows in the Bransfield Strait. In this study, we report our new CTD and LADCP measurements performed in 2022 over the watersheds between the basins. Quasisimultaneous observations of the main circulation patterns carried out at several sections allowed us to analyze the evolution of thermohaline and kinematic structures along the Bransfield Strait. Volume transports of waters in the strait were estimated on the basis of direct velocity observations. These new data also indicate the existence of intense and variable deep current between the central and eastern basins of the strait. The analysis of historical data shows that the mean flow is directed from the central to the eastern basin. In addition, LADCP data suggest the intensification of the flow in the narrow part of the sill between the basins, and the possible mixing of deep waters at this location.